All-carbon microporous graphitic photocatalyst-promoted reduction of CO2 to CO in the absence of metals or dopant elements. Issue 32 (2nd August 2022) - Garcia-Mulero, Ana; Asiri, Abdullah M.; Albero, Josep; Primo, Ana; Garcia, Hermenegildo
Abstract : Microporous graphitic carbon derived from cyclodextrins exhibited photocatalytic activity in CO2 reduction upon irradiation in the presence of triethanolamine, forming H2 (19 μmol h −1 ), CO (23 μmol h −1 ) and CH4 (4 μmol h −1 ). Abstract : Microporous graphitic carbon (mp-C) derived from the pyrolysis of α-, β-, and γ-cyclodextrins exhibited photocatalytic activity in CO2 -saturated acetonitrile–water upon irradiation with UV-Vis light and in the presence of triethanolamine, forming H2 (19 μmol h −1 ) and CO (23 μmol h −1 ) accompanied by a lesser proportion of CH4 (4 μmol h −1 ). The most efficient was the mp-C material derived from α-cyclodextrin (mp-Cα ) and having a pore dimension of 0.68 nm. The process also occured, although to a much lesser extent, under simulated sunlight or with UV-Vis irradiation in the absence of a sacrificial agent, with H2 O being the electron donor. The origin of the CO was proved by isotopic 13 C labelling experiments. Photocurrent measurements proved the occurrence of charge separation and the increase in photocurrent intensity in the presence of CO2 . Transient absorption spectroscopy was used to detect the charge separate state decay in the microsecond time scale and proved that a fraction of the photogenerated electrons were able to react with CO2 .